2016
DOI: 10.1080/21501203.2016.1247116
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and evaluation of Metarhizium anisopliae (Metsch.) Sorokin strains for their temperature tolerance

Abstract: Entomopathogenic fungal species from the genera Beauveria, Metarhizium and Lecanicillium are important components in biological control of insect pests. However, temperature, humidity and UV radiation are among the important abiotic factors, which limit their effective usage. In this study, four local isolates of Metarhizium were isolated from different crop rhiospheres of Telangana and Andhra Pradesh states of India, identified and tested for their temperature tolerance in terms of radial growth, conidial yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…3). This finding in the present study was not compatible with Chandra Teja & Rahman (2016) who found that all isolates were closer to each other. Fig.…”
Section: Phylogenetic Analysiscontrasting
confidence: 99%
“…3). This finding in the present study was not compatible with Chandra Teja & Rahman (2016) who found that all isolates were closer to each other. Fig.…”
Section: Phylogenetic Analysiscontrasting
confidence: 99%
“…The tolerance of these strains to temperature was higher than that reported by Dimbi et al (2004) for M. anisopliae isolates. However, higher tolerance to temperature in EF strains from tropical and equatorial areas has already been shown (Rangel et al, 2005;Teja and Rahman, 2016).…”
Section: Effect Of Temperature On Ef Strains Germination and Growthmentioning
confidence: 98%
“…Temperature plasticity in EF strains may help buffer detrimental effects of temperature variation in the field, and it has received considerable attention over recent decades (Alali et al, 2019;Dimbi et al, 2004;Ekesi et al, 1999;Teja and Rahman, 2016). However, most studies evaluated in vitro germination and mycelial growth only at constant temperatures, allowing defining critical or threshold temperatures.…”
Section: Effect Of Temperature On Fungal Virulence and Control Effici...mentioning
confidence: 99%
“…In our study, 32 and 34 °C temperatures were unfavorable in the growth of all strains evaluated; in particular, LBM-5, LBM-12, LBM-41, LBM-127, LBM-146 and LBM-267 were especially sensitive to 34 °C (p ≤ 0.05). It has been noted that most entomopathogenic fungi are mesophilic with growth between 10 and 40 °C and an optimum between 25 and 35 °C (Chandra and Rahman, 2016). Strains treated at 34 °C had a marked decrease in growth.…”
Section: Effect Of Temperature On the Growth Of Metarhizium Anisoplia...mentioning
confidence: 99%